2008
DOI: 10.1016/j.ejheart.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on plasma levels of asymmetric dimethylarginine in patients with non‐ischaemic heart failure

Abstract: Background: Elevated plasma levels of asymmetric dimethylarginine (ADMA), an endothelial nitric oxide synthase (eNOS) inhibitor, may contribute to endothelial dysfunction in chronic heart failure (CHF). Since statins upregulate eNOS and ameliorate endothelial dysfunction in non-ischaemic CHF, we hypothesized that this may be in part through modification of ADMA. Aim: To evaluate the effect of atorvastatin on the relationship between ADMA and endothelial function in non-ischaemic CHF. Methods: Twenty-four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
1
21
1
Order By: Relevance
“…However, the results of human studies have been contradictory. Some randomized trials have demonstrated that shortterm statin treatment lowers circulating ADMA levels in humans (61, 76, 112), while other studies have failed to find such an effect (36,74,85,109,121). These discordant results could possibly be attributed to differences in the characteristics of the populations examined.…”
Section: Effects Of Statins On Enoscontrasting
confidence: 39%
“…However, the results of human studies have been contradictory. Some randomized trials have demonstrated that shortterm statin treatment lowers circulating ADMA levels in humans (61, 76, 112), while other studies have failed to find such an effect (36,74,85,109,121). These discordant results could possibly be attributed to differences in the characteristics of the populations examined.…”
Section: Effects Of Statins On Enoscontrasting
confidence: 39%
“…In the majority of the studies, no impact on the ADMA levels was observed with statin therapy [89][90][91][92]. However rosuvastatin appeared to reduce ADMA levels in one study [93].…”
Section: Modulation Of Adma Levels By Pharma-cotherapy Statin Therapymentioning
confidence: 99%
“…Duration of trials ranged between 6 weeks and 24 months. Six trials were designed as parallel-group studies 22,25,27,[29][30][31] and 2 trials as cross-over studies 23,28 . One study 26 was a prospective follow-up trial conducted in 3 stages.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The number of participants in these trials ranged from 53 to 650. The included studies were published between 2003 and 2012, and were conducted in Norway, Taiwan, the Netherlands, Bulgaria, Italy Turkey, New Zealand, China and Finland [22][23][24][25][26][27][28][29][30] . Statins (pravastatin, rosuvastatin, simvastatin, fluvastatin, and atorvastatin) were administered at doses from 10 to 80 mg/day.…”
Section: Description Of Studiesmentioning
confidence: 99%